Urgensi Implementasi Pendidikan Agama Islam terhadap Pembentukan Akhlak dan Sopan Santun Siswa di SMP Negeri 1 Sitiung Dharmasraya - Wensi, Edmily; M, Iswantir; Neli, Ana Fitri (Al-DYAS, 2023)
In this study, it discusses the Importance of Islamic Religious Education in the Formation of Morals and Manners of Students at SMP N 1 SITIUNG. The problem in this study is "Islamic Religious Education implemented in SMP N 1 SITIUNG and its influence on the formation of student morals and manners, and how important Islamic Religious Education is to the formation of student morals and manners. This research is motivated by the author's suspicion that there are still students at SMP N 1 SITIUNG whose morals and manners are lacking in participating in PAI learning at school. This study aims to determine whether there is an influence of Islamic Religious Education on the formation of morals and manners of students at SMP N 1 Sitiung and to find out how important Islamic Religious Education is on the formation of morals and manners of students at SMP N 1 Sitiung. This research method uses qualitative methods with a descriptive approach. The population of this research is students of SMP N 1 Sitiung. Collecting data using observation, interviews and documentation. The research results show evidence of: 1). The importance of Islamic religious education at SMP N 1 Sitiung to improve the morals and manners of students at school, 2). The importance of Islamic religious education for the formation of student morals and manners.